2018
DOI: 10.1108/nfs-09-2017-0203
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index in relation to obesity and body mass index: a meta-analysis

Abstract: Purpose Studies investigating the association between dietary inflammatory index (DII) and body mass index (BMI) have led to inconsistent findings. Therefore, to decisively conclude, this paper aims to clarify the relationship between DII and obesity by performing meta-analysis. Design/methodology/approach PubMed, Scopus and Google Scholar were searched up to July 2017 using key words selected from Medical Subject Headings and other related keywords to identify all relevant articles. In total, 22 articles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…Silva Oliveira et al conducted a study on 3151 university graduates, and found that there was a significant correlation between DII and physical activity (24), which are consistent with our results. Also, Varkaneh et al conducted a study on 198 women with a mean age of 33.4 years who referred to medical centers, and the results showed that there was a significant relationship between DII and physical activity (4). The present study showed that people with moderate to vigorous physical activity had a lower DII score.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Silva Oliveira et al conducted a study on 3151 university graduates, and found that there was a significant correlation between DII and physical activity (24), which are consistent with our results. Also, Varkaneh et al conducted a study on 198 women with a mean age of 33.4 years who referred to medical centers, and the results showed that there was a significant relationship between DII and physical activity (4). The present study showed that people with moderate to vigorous physical activity had a lower DII score.…”
Section: Discussionsupporting
confidence: 56%
“…The prevalence of overweight and obesity in adults was reported at 39% and 13%; respectively, by WHO in 2016 (1,2). The prevalence of overweight and obesity in Middle Eastern countries is 54% among women and 31% among men, and can be traced to the deaths of 150,000 people in these countries (3,4). More than half (63.2%) of individuals aged 15-65 years old were reported to be overweight and obese according to the first national study and the study of glucose and lipids in Tehran.…”
Section: Introductionmentioning
confidence: 99%
“…High circulating acute phase inflammatory markers, i.e., C-reactive protein and fibrinogen have been linked to chronic inflammatory diseases such as MetS, diabetes, obesity, and CVD [50][51][52]. [53] suggesting that vitamin D is an anti-inflammatory agent [54].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several (systematic) reviews and meta-analyses have been conducted to appraise evidence to date for the associations between DII and cardiometabolic disease [11,169,170,171]. Of these, three reviews focused on CVD, MetS, and mortality [11,170,171], while the other focused on obesity and body mass index (BMI) [169].…”
Section: And Cardiometabolic Health and Diseasementioning
confidence: 99%
“…Recently, several (systematic) reviews and meta-analyses have been conducted to appraise evidence to date for the associations between DII and cardiometabolic disease [11,169,170,171]. Of these, three reviews focused on CVD, MetS, and mortality [11,170,171], while the other focused on obesity and body mass index (BMI) [169]. In general, a more pro-inflammatory diet, as indicated by a higher DII score, has been associated with higher risk of obesity [169], CVD risk, and CVD-related mortality [11,170,171], while the relationship between DII and MetS is less consistent [170,171].…”
Section: And Cardiometabolic Health and Diseasementioning
confidence: 99%